CAUSALITY BETWEEN DOMESTIC INVESTMENT AND ECONOMIC GROWTH IN ARAB COUNTRIES - Bakari, Sayef; El Weriemmi, Malek (Journal of Malikussaleh Public Economics, 2024)
The aim of this investigation is to examine the nexus between domestic investment and economic growth in Arab countries. To attempt our goal, we used annual data for the period 1990 - 2020 and Vector Error Correction Model. Empirical analysis indicates that there is no relationship between domestic investment and economic growth in the long run. However, we find a bidirectional causality between domestic investment and economic growth in the short run. These results provide evidence that domestic investment is necessary in Arab countries economy and is presented as an engine of growth since they cause economic growth in the short term. But they are not carried out and treated with a solid and fair manner, which offer new insights into Arabe countries investment policy for promoting economic growth.